2022
DOI: 10.3390/ijerph191811794
|View full text |Cite
|
Sign up to set email alerts
|

Shifting the Focus: A Pilot Study on the Effects of Positive Body Exposure on Body Satisfaction, Body Attitude, Eating Pathology and Depressive Symptoms in Female Patients with Eating Disorders

Abstract: One of the most commonly used techniques for the treatment of body image problems in eating disorders (ED) is body exposure (BE). However, evidence of its effectiveness in clinical populations is scarce. In the Positive Body Experience (PBE) protocol, the focus of positive BE is on aesthetic, functional and tactile aspects of the body. The current study evaluates the outcomes of positive BE with regard to changes in attitudinal body image and eating pathology, as well as the factors that influence these change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Based on the scientific evidence presented so far, tailored comprehensive multidisciplinary treatment is essential to provide adequate care for patients with obesity and BED by addressing their overweight and its consequences. This interdisciplinary approach should combine a structured lifestyle treatment plan with healthy meal planning, PA, and behavioral interventions, according to a multidisciplinary team of experts [66,67]. They suggested that measurements for multidisciplinary interventions of adolescents with BED should consider weight loss as well as behavioral and mental improvements.…”
Section: Binge Eating Disorder (Bed)mentioning
confidence: 99%
“…Based on the scientific evidence presented so far, tailored comprehensive multidisciplinary treatment is essential to provide adequate care for patients with obesity and BED by addressing their overweight and its consequences. This interdisciplinary approach should combine a structured lifestyle treatment plan with healthy meal planning, PA, and behavioral interventions, according to a multidisciplinary team of experts [66,67]. They suggested that measurements for multidisciplinary interventions of adolescents with BED should consider weight loss as well as behavioral and mental improvements.…”
Section: Binge Eating Disorder (Bed)mentioning
confidence: 99%
“…Furthermore, measuring body functionality creates the possibility to monitor the effectiveness of therapeutic interventions which focus on functional aspects of body image to enhance body satisfaction. In this light, Rekkers et al [7,14] developed andvaluated a protocol based on positive body exposure in which body functionality forms an important and innovative part. Recently, Walker and Murray [8] developed a novel body functionality-focused mirror exposure, integrating a complete focus on body functionality with mirror exposure.…”
mentioning
confidence: 99%